2001
DOI: 10.1068/a33164
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Flexibility in Job Mobility: Macrolevel Opportunities and Microlevel Restrictions

Abstract: Disequilibria among regional labour markets persist through spatial inflexibility in job mobility resulting from restrictions in migration and long-distance commuting. This contribution analyses workplace mobility—the acceptance of a job at a great distance from the place of residence—using a direct measure which includes both migration and long commutes as means for covering this distance. Two sources of spatial inflexibility are identified. The first is a low overall chance of general job mobility; the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…For example, the average distance moved is often found to increase in a linear manner with levels of educational attainment and household income (Fielding, 2012). Individuals with higher educational attainment and associated occupations are known to search over far wider labour markets and have greater spatial flexibility associated with, and driven by, career progression (van Ham et al, 2001). This compares to those in the more routine and manual occupations, who are generally more spatially tied to certain locales and local labour markets (Fielding, 2012).…”
Section: Intervening Distance and Selective Micro-level Dynamicsmentioning
confidence: 99%
“…For example, the average distance moved is often found to increase in a linear manner with levels of educational attainment and household income (Fielding, 2012). Individuals with higher educational attainment and associated occupations are known to search over far wider labour markets and have greater spatial flexibility associated with, and driven by, career progression (van Ham et al, 2001). This compares to those in the more routine and manual occupations, who are generally more spatially tied to certain locales and local labour markets (Fielding, 2012).…”
Section: Intervening Distance and Selective Micro-level Dynamicsmentioning
confidence: 99%
“…England (1993) for instance, has shown that commuting times for women in suburban areas largely vary and for various reasons. The dual earner strategy hypothesis suggests that dual earners choose strategic suburban residential locations in between larger cities because these are the locations with the highest job access for those willing to invest in commuting (Van Ham et al, 2001a, 2001bVan Ham, 2002). From a dual earner strategy perspective it is therefore expected that living in an area with a high job access within 45 minutes increases the likelihood of symmetric fulltime working arrangements and symmetric far commuting arrangements.…”
Section: Residential Context: Opportunities and Constraintsmentioning
confidence: 99%
“…Furthermore, homeowners might be less likely to move because they are more attached to their residential location and their residence than renters. As a result of limited spatial flexibility in terms of moving house, homeowners might be more likely to choose long commutes than renters (Van Ham & Hooimeijer, 2005). Being a homeowner is therefore expected to increase the likelihood of a symmetric fulltime working arrangement and a commuting arrangement in which one or both partners have a far commute.…”
Section: Socio-economic Characteristics and Working And Commuting Arrmentioning
confidence: 99%
See 2 more Smart Citations